Combining Traditional and Molecular Techniques Supports the Discovery of a Novel Legionella Species During Environmental Surveillance in a Healthcare Facility - Girolamini, Luna; Pascale, Maria Rosaria; Mazzotta, Marta; Spiteri, Simona; Marino, Federica; Salaris, Silvano; Grottola, Antonella; Orsini, Massimiliano; Cristino, Sandra (Frontiers in Microbiology, 2022)
Legionella surveillance plays a significant role not only to prevent the risk of infection, but also to study the ecology of isolates, their characteristics, and how their prevalence changes in the environment. The difficulty in Legionella isolation, identification, and typing results in a low notification rate, therefore human infection is still underestimated. In addition, during Legionella surveillance, the special attention given to Legionella pneumophila leads to an underestimation of the prevalence and risk of infection for other species. This study describes the workflow performed during environmental Legionella surveillance that resulted in the isolation of two strains, named 8cVS16 and 9fVS26, associated with the genus Legionella. Traditional and novel approaches such as standard culture technique, MALDI-TOF MS, gene sequencing, and Whole-genome sequencing (WGS) analysis were combined to demonstrate that isolates belong to a novel species. The strain characteristics, the differences between macrophage infectivity potential (mip), RNA polymerase β subunit (rpoB), and reference gene sequences, the average nucleotide identity (ANI) of 90.4%, and the DNA-DNA digital hybridization (dDDH) analysis of 43% demonstrate that these isolates belong to a new Legionella species. The findings suggest that during the culture technique, special attention should be paid to the characteristics of the isolates that are less associated with the Legionella genus in order to investigate the differences found using more sensitive methods. The characterization of the two newly discovered isolates based on morphological, biochemical, and microscopic characteristics is currently underway and will be described in a separate manuscript.